Desenvolvimento do Brasil: a importância da indústria na economia - Miranda, André Araújo [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The general objective of this paper is to discuss the development and influence of the industry in this process. Specifically, is to show the great importance of this sector in the economic growth. Through the technical analysis of the sectors of the economy, of the literature and historical analysis, it can be concluded that in fact, the secondary sector has a huge effect on development

O objetivo geral desse trabalho é discutir desenvolvimento e a influência da indústria dentro desse processo. Especificamente, é mostrar a grande importância desse setor no crescimento. Através das análises técnica dos setores da economia, da literatura sobre o tema e histórica, conclui-se que de fato, o setor secundário tem um enorme efeito no desenvolvimento
Keywords: Economia; Indústrias; Industrialização; Industrialization